Redução de metabissulfito de sódio no processamento industrial de batatas - Nascimento, Revenli Fernanda do (2017)
The industrially processed potato presents great susceptibility to the browning reactions, which damage the quality of the final product. To avoid interferences in the quality of the product the food industries they use the sodium metabisulphite (MBS) as inhibitor of both reactions. However, this additive one can cause environmental and human health hazards. Due to the interest of a located agribusiness in the State of Paraná, in reducing the amount of this additive in the processing of ready-to-eat potatoes this work had for aim to minimize the concentration of MBS used in the processing of potatoes seeking a final product of quality. For this purpose, we tested in the process of immersion of the potatoes the following chemical treatments: T1 (without treatment or control), T2 (0,5% of ascorbic acid), T3 (reduction of 50% of the concentration of MBS), T4 (reduction of 50% of the concentration of MBS + 0,5% of ascorbic acid), T5 (reduction of 75% of the concentration MBS + 0,25% of ascorbic acid) and T6 (industrial Pattern just containing MBS). To evaluate the quality of the products the contents of total soluble solids, pH, titratable total acidity, instrumental color, browning index, yellowing index, instrumental firmness and the concentration of residual sulfur dioxide (SO2) were quantified. For the analyses of the data a factorial planning was accomplished 22 with three central points, following by the analysis of variance univariate and multivariate. The results indicated that the studied antioxidants did not affect the content of total soluble solids, the titratable total acidity and the firmness of the food, however, they influenced the pH, the color, the browning index and the yellowing index of the potatoes significantly. From the data generated by the univariate and multivariate statistical analysis it was concluded that the the treatment T5 (0,0) can be considered as the potential substitute of the treatment T6 (industrial pattern), allowing the reduction of 74% of the concentration residual SO2 in the industrial production of potatoes.